Nature, Aesthetics, and Ecological Ethics: Michael Northcott, and Robert Doran in Dialogue - Whelan, Gerard (Filosofia, 2019)
This issue of “Filosofia” is dedicated to the theme “Images of Nature”. While issuing the call for papers, the editor explained the choice of the theme as follows: “the problem of ecological crisis that arises nowadays has forced philosophy to break out of the classic schemes of modernity, developing new categories and a renewed philosophy of nature”. The editor adds: “nature becomes a thought-laboratory, from which to think new ethical, political, aesthetic, and metaphysical perspectives”. In this article, I introduce the thought of two thinkers who exhibit the characteristics identified by the editor. The first is Michael Northcott, an important English-speaking ecological ethicist; the second is Robert Doran, a Jesuit theologian, whose critical realist thought can help to provide foundations for the orientations found in Northcott. Taken together, their reflections are worthy of consideration by those who consider their thought as a renewal of the philosophy of nature for nowadays.